BARRIERS TO ICT ADOPTION BY SMEs IN INDONESIA: HOW TO BRIDGE THE DIGITAL DISPARITY? - Muljono, Wiryanta; Setiyawati, Sri; Sudarsana, Sudarsana; Setiawati, Priyanka Pertiwi (Jurnal Aplikasi Manajemen, 2021)
The use and utilization of ICT for SMEs attract the attention of many parties. The problems of SMEs in Yogyakarta, Indonesia that is so diverse cannot be simplified on the issue of technology adoption. Moreover, increasing competitiveness is necessary so that ICT can truly be a bridging digital disparity. The action research activity is carried out to close the gap which not only focuses on understanding the pattern of technology adoption alone but also involves action steps in helping SMEs to survive and able to compete. The results showed that the SMEs still had difficulty in utilizing ICT from the upstream side. This is triggered by the limitations of existing human capital in managing technical and operational aspects of ICT. Therefore, the strategies to use of ICT for SMEs is recommended to combine a proactive and reactive approach so that the optimization of resources will be achieved. Accordingly, we suggest that further studies apply the implementation of ICT on proactive and reactive actions to close the knowledge gap between the two in a different setting, context, location, and/or culture.